2014
DOI: 10.1093/iwc/iwu038
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the First-Person Perspective in Dementia: A Qualitative Personal Evaluation Game to Evaluate Assistive Technology for People Affected by Dementia in the Home Context

Abstract: Seeing the first-person perspective in dementia : a qualitative personal evaluation game to evaluate assistive technology for people affected by dementia in the home context. Interacting with Computers, 27(1), 47-59.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“… 36 Suijkerbuijk et al (2015) asked users with MCI/D to evaluate their use of a dynamic lamp, which aimed to improve sleep/wake rhythms, by answering questions playing a personal evaluation game on an iPad (“Angenaam”) (eight couples) or answering a questionnaire using a tablet (four couples). 51 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 36 Suijkerbuijk et al (2015) asked users with MCI/D to evaluate their use of a dynamic lamp, which aimed to improve sleep/wake rhythms, by answering questions playing a personal evaluation game on an iPad (“Angenaam”) (eight couples) or answering a questionnaire using a tablet (four couples). 51 …”
Section: Resultsmentioning
confidence: 99%
“…Many of the studies explicitly aimed to evaluate the usability of the technologies that were explored. 19 , 28 , 38 , 40 , 43 , 47 , 49 , 51 Cavallo et al (2015) found that perceived usability could improve QoL for people with MCI/D and their FCs. 19 Cavallo et al (2015), 19 Leuty et al (2013), 47 and Lindqvist et al (2015) 43 used the same definition as this review regarding usability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring inclusive approaches to actively engage people with dementia in participatory design has been a growing area of research, e.g. [12,31,33,55,56]. Participatory sessions that center around creativity and expression minimize the burden of participants by providing meaningful activity in a comfortable, enjoyable and social setting [37].…”
Section: Involving People With Dementia In Designmentioning
confidence: 99%
“…By the end of this successful project in December 2015 several innovations had been developed and tested at home [6][7][8] and some have already been implemented into the daily care for PWD.…”
Section: Introductionmentioning
confidence: 99%